Integration of strategic business planning and technology planning in globally operating companies by means of roadmapping. (7th November 2007) - Specht, Dieter; Kadlubski, Astrid; Behrens, Stefan
The following article introduces and investigates an approach to the successful management and coordination of strategic business and technology planning. First, the theoretical framework is given. Then, an approach is introduced to integrate technology planning into strategic business planning. The article is concluded by a critical assessment of the approach introduced.